Use of mechanical ventilation in pediatric patients - Martić Jelena; Janković Borisav; Minić Predrag; Sovtić Aleksandar; Nikolić Ljubica; Ristić Snežana; Sarajlija Adrijan (Vojnosanitetski Pregled)
Background/Aim. Major aims of mechanical ventilation (MV) in pediatrics mean the contribution to complete recovery of acute disorder or to establishing stability of previously long-term changed health condition. MV is used today in 16-46% of patients treated in pediatric intensive care units. The aim of this paper was to get insight into the presence of the disease and pathologic conditions and outcome of MV regarding previous health condition of pediatric patients. Methods. This retrospective study included 476 pediatric patients (beyond neonatal age) who underwent mechanical ventilation (MV). On the basis of previous health status the patients were classified in two groups: the group A consisted of 157 children with no previous chronic disease leading to MV and the group H comprised of 319 children who received MV due to worsening of previous chronic disease. Results. In both groups of pediatric patients there was significant predominance of younger age patients. Acute and chronic neurological disorders were the most frequent conditions requiring use of MV. Out of a total number (476) of the patients, 178 patients (37.4%) died. In the group A 17 patients (10.9%) died, while in the group H mortality rate was significantly higher (161 or 50.5% patients died; p < 0.01; RR 4.85; CI 3.1-7.6). Total duration time of MV in all the patients was 7 525 days, with 1 345 days (15%) accounted for the group A and 4 567 days (85%) for the group H. Mean MV duration was 7.48 (± 9.23) days for the patients in the group A which is significantly shorter in comparison to mean 21.8 (± 57.96) days for the group H patients (p < 0.001). Conclusion. These results point out significant contribution of MV to better outcome in pediatric patients with different acute disorders. Clear dominance of chronically ill children requiring mechanical ventilation due to acute worsening of their condition implies new complexity of problems regarding organization of pediatric intensive care and treatment.